The impact of contextual fragility on development in practice: perspectives from Zimbabwe. Issue 8 (17th November 2018) - Madziva, Cathrine
ABSTRACT: This article explores the impact of contextual fragility on development in practice in the context of partnership working. The utilisation of oppressive legislation and stringent registration for CSOs by a state fearful of losing political hegemony resulted in limited community participation and CBO reluctance to engage in advocacy activities deemed political despite northern partner eagerness. Financial distress led to a partnership termination, partial and non-implementation of some development activities. Utilising contextual analysis to unmask the heterogeneous nature of fragile contexts can be a valuable starting point in capturing unique complexities and irregularities in each context to inform programme planning.